A ULF wave driver of ring current energization. Issue 19 (13th October 2014) - Murphy, Kyle R.; Mann, Ian R.; Ozeke, Louis G.
Abstract ULF wave radial diffusion plays an important role in the transport of energetic electrons in the outer radiation belt, yet similar ring current transport is seldom considered even though ions satisfy a nearly identical drift resonance condition albeit without the relativistic correction. By examining the correlation between ULF wave power and the response of the ring current, characterized by Dst, we demonstrate a definite correlation between ULF wave power and Dst. Significantly, the lagged correlation peaks such that ULF waves precede the response of the ring current and Dst. We suggest that this correlation is the result of enhanced radial transport and energization of ring current ions through drift resonance and ULF wave radial diffusion of ring current ions. An analysis and comparison of the ion and electron diffusion coefficients further support this conclusion, ULF waves providing an important missing physical transport process explaining Dst underestimation in ring current models.